Model Struktural Interpretif untuk Menganalisis Faktor-faktor Pengaruh Media Sosial terhadap Self-Esteem Remaja - Yudatama, Uky; Sugiarti, Rini; Suhariadi, Fendy (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
Self-esteem is an important aspect of adolescent mental health and can be influenced by various factors related to social media use. Through a literature review and interviews, data were collected and then analyzed using the Interpretive Structural Modeling (ISM) approach to build a structural model depicting the interactions among these factors. The literature review identified nine key factors: Feelings of Loneliness, Types of Social Media Interactions, Content Consumed, Social Support from Social Media, Social Comparison, Cyberbullying, Control over Social Media Use, Parental Involvement, Intensity of Social Media Use, and Identity Development. The ISM model revealed that the factor of feelings of loneliness (F1) is at the fourth or most fundamental level in the hierarchy of factors, while the intensity of social media use (F9) is at the highest level. Therefore, the role of parental involvement (F8) is a crucial foundation to address feelings of loneliness (F1), because if adolescents feel lonely, they may turn to social media as an escape, which can negatively impact self-esteem if not properly controlled. These findings are expected to contribute to the development of effective intervention strategies to enhance adolescent self-esteem.